CONTEMPORARY TRENDS IN THE USE OF INFORMATION AND COMMUNICATION TECHOLOGIES IN MEDICAL EDUCATION - Ilić, Nikola; Bajčetić, Miloš; Milić, Nataša (Medicinski podmladak, 2024)
Last decade of the 20th century brought to education new technologies. Those came on the wave of ever more affordable computers and mobile technologies that followed with the emergence of the internet. During the COVID-19 pandemia we had yet another development acceleration of ICT services in education and mass digitalization of educational materials. Now, we are witnessing new breakthrough of artificial intelligence and machine learning in both teaching processes and clinical practice.
Keywords: medical education; information and communication technologies; online education